The Volatile Sulphur Compounds of Oysters - Ronald, A. P.; Thomson, W. A. B. (Journal of the Fisheries Research Board of Canada, 1964)
The compound responsible for the characteristic odour of fresh Pacific oysters, Crassostrea gigas (Thunberg), has been identified as dimethyl sulphide [(CH 3 ) 2 S], by the formation of mercury salts, and by infrared analysis and gas chromatography. The effect of bacterial action on the oysters has been observed and a number of the volatile organo-sulphur decomposition compounds, produced during room storage at 20–21 °C, have been identified by gas chromatography and by the formation of their lead and mercury salts.